Mr. Gumpy's outing - Burningham, John. (New York : Henry Holt, 1990)
Mr. Gumpy accepts more and more riders on his boat until the inevitable occurs.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
Book Links (A.L.A.), July 2006.
Booklist, April 2007.
Bulletin (Center for Children's books), August 2007.
Keywords: Boats and boating -- Juvenile fiction; Boats and boating -- Fiction; Boats and boating -- Fiction